Revisiting the inflation perception conundrum - Kim Abildgren; Andreas Kuchler (Danmarks Nationalbank, 2019)
Several studies have found that the levels of inflation perceived by households persistently exceed observed inflation levels measured by official Consumer Price Indices. In this paper, we revisit the issue based on rich and previously unexplored household-level data from the Danish part of the EU-Harmonised Consumer Expectations Survey (CES) linked to microdata from Danish administrative registers. We find that accounting for even several of the factors usually put forward to explain the overestimation bias can only reduce it slightly. Food prices seem to carry a larger weight in perceived inflation than in the official CPI, and we find clear seasonal effects in the inflation perception bias. The bias is also reflected in the households' expectations of the future inflation level. One should therefore not use the levels of survey-based inflation expectations from the CES in empirical works. We find a much smaller bias in the expectations regarding future changes in inflation rates. Implementing some form of guidance on the current or typical rate of inflation in the survey questions might reduce the bias. However, the bias might also indicate a more general need for enhanced communication by monetary authorities and statistical agencies regarding the rather abstract concept of "inflation".
Keywords: D12; E31; 330; Inflation perceptions; Inflation expectations; Micro data